2023
DOI: 10.3847/1538-4357/acac77
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Dynamical Cooling in the Dynamics of Circumbinary Disks

Abstract: Hydrodynamical interactions between binaries and circumbinary disks (CBDs) play an important role in a variety of astrophysical systems, from young stellar binaries to supermassive black hole binaries. Previous simulations of CBDs have mostly employed locally isothermal equations of state. We carry out 2D viscous hydrodynamic simulations of CBDs around equal-mass, circular binaries, treating the gas thermodynamics by thermal relaxation toward equilibrium temperature (the constant-β cooling ansatz, where β is t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Circumbinary disk-driven outspirals were first observed in Miranda et al (2017) and later confirmed by numerous other studies (e.g., Moody et al 2019;Muñoz et al 2019;Duffell et al 2020). Subsequent studies have found that binary orbital evolution depends on the disk and binary parameters, such as the disk aspect ratio h/r (Tiede et al 2020;Dittmann & Ryan 2022, 2024Penzlin et al 2022), the disk viscosity (Miranda et al 2017;Dittmann & Ryan 2022, 2024Franchini et al 2022;Penzlin et al 2022), the cooling timescale (Sudarshan et al 2022;Wang et al 2023aWang et al , 2023bFranchini et al 2024), and the binary eccentricity (Miranda et al 2017;D'Orazio & Duffell 2021;Siwek et al 2023a). Lai & Muñoz (2023) recently presented a review summarizing the outcomes of many of these studies.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Circumbinary disk-driven outspirals were first observed in Miranda et al (2017) and later confirmed by numerous other studies (e.g., Moody et al 2019;Muñoz et al 2019;Duffell et al 2020). Subsequent studies have found that binary orbital evolution depends on the disk and binary parameters, such as the disk aspect ratio h/r (Tiede et al 2020;Dittmann & Ryan 2022, 2024Penzlin et al 2022), the disk viscosity (Miranda et al 2017;Dittmann & Ryan 2022, 2024Franchini et al 2022;Penzlin et al 2022), the cooling timescale (Sudarshan et al 2022;Wang et al 2023aWang et al , 2023bFranchini et al 2024), and the binary eccentricity (Miranda et al 2017;D'Orazio & Duffell 2021;Siwek et al 2023a). Lai & Muñoz (2023) recently presented a review summarizing the outcomes of many of these studies.…”
Section: Introductionmentioning
confidence: 61%
“…The two appear to be causally linked, but the details depend on the disk and binary parameters. In some cases, disks that are stable and do not achieve an eccentric cavity morphology result in inward migration (Franchini et al 2022;Wang et al 2023b;Dittmann & Ryan 2024).…”
Section: The First 100 Orbitsmentioning
confidence: 99%
“…W see Figure 4). Lastly, we note that because the precession rate is dominated by the outward radial pull of the CBD, we expect our results to be comparatively insensitive to system uncertainties like the disk thermodynamics (unlike the other orbital elements; see, e.g., Tiede et al 2020;Dittmann & Ryan 2022;Wang et al 2023) or whether the binary is prograde or retrograde (Appendix B).…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, Huang & Yu (2022) explored the effect of cooling on the Rossby wave instability (RWI) in PPDs through linear analysis. Sudarshan et al (2022) and Wang et al (2023) initiated studies on how thermodynamics affects the accretion of binary systems using numerical simulations. In addition to the parameterized β −cooling method mentioned above, some studies adopt realistic terms for heating and cooling in the energy equation (Ziampras et al 2020(Ziampras et al , 2023.…”
Section: Introductionmentioning
confidence: 99%